(untitled) (Orthodontic Journal of Nepal, 2021)
Introduction: Cephalometric tracing is an indispensable method for the evaluation of the growth and development of the facial skeleton. The clinical implication of the tracing may be utilized in many branches of dentistry for diagnosis and treatment planning. The research based cephalometric tracing has been widely used over a period of time by various specialist. The purpose of this study was to compare the cephalometric tracing method between manual and the digital method. Materials and Method: Lateral cephalometric radiographs of 120 patients who came for orthodontic treatment during Jan 2020 to Dec 2020 were randomly selected from Tribhuvan University Dental Teaching Hospital and one orthodontic center. Only the cephalograms with clarity and without artefacts were selected. The samples were randomly selected without any discremation of gender, occlusal type or skeletal pattern. The two methods were compared in terms of reproducibility and the speed of cephalometric tracing. The cephalograms were compared using both the manual and the digital method using Vistadent OC 1.1 software program (GAC International Inc, Bohemia, New York, USA). The mean tracing time for each method was also estimated. Paired t –test was used to compare the differences in individual measurement between the two methods. Intraclass correlation coefficients were used to measure the repeatability of the measurements. Results: On comparing two methods, 3 out of 20 measurements showed statistically significant difference while others showed no statistically significant difference. The mean time needed to perform cephalometric analysis by the digital method (4.61±0.63 minutes) was significantly less as compared to the manual method (11.23±0.71 minutes) and the difference of performance duration were statistically significant (<0.05). Intraclass correlation coefficient showed strong correlation (0.86 to 0.99) for each repeated cephalometric measurements carried out by both manual and digital methods. Conclusion: Both conventional manual and digital cephalometry methods showed good reproducibility with strong correlation for repeated measurements. The digital method exhibited significant reduction in time compared to manual method. Incorporation of digital methods by the clinicians can increase their efficiency